Gadget Use Duration and its Impact on Learning Motivation and Social Development of Children - Tri Peni; Siti Indatul Laili; Tri Ratnaningsih (Journal of Ners and Midwifery, 2022)
Development in communication technology such as smartphones and the internet are able to easily solve all information needs. However, there are many misuses of the sophistication of these tools by many children. This study aimed to determine the impact of using gadgets on learning motivation and children's social development at Islamic Elementary School Yaabunayya Mojokerto. The design of the study used cross-sectional analysis. The population was all students at Islamic Elementary School Yaabunayya with a total of 146 children. The sampling technique used purposive sampling with the inclusion criteria of children in grades two to six who were willing to be researched with the consent of their parents.Â  Samples that meet the inclusion criteria were 85 respondents. The instruments used were the Motivated Strategies for Learning Questionnaire (MSLQ) and Vineland Social Maturity Scale (VSMS). Data analysis used the Spearman Rho test. The results of the analysis found that there was a correlation between the duration of using gadgets and the social development of children with a Ï value (0.013). Children who donâ€™t play with gadgets tend to look for playmates who can improve social development. The results of the study there is no correlation between the duration of gadget use and learning motivation in children with a Ï value (0.095). This is because children use gadgets to get lots of interesting lessons on the internet. For this reason, parents are expected to always accompany their children in using gadgets.